Contractual renegotiations and International investment arbitration : a relational contract theory interpretation of investment treaties - Florou, Aikaterini (Institut d'études politiques, 2017)
The relationship between international investment treaties and the underlying contracts remains a highly disputed matter in international investment law. This thesis explored the contract-treaty interaction by using the renegotiation of regulatory contracts in the sector of energy infrastructure as a natural experiment, with a particular emphasis on the arbitral disputes that arose from the Argentine crisis. It deployed to this end an original analytical framework drawing from transaction cost economics and relational contract theory. The result of the novel combination of these two analytical frameworks is the construction of an interpretative methodology that takes an integrated approach to the two instruments – the contract and the overarching treaty – in a way that achieves a more sustainable balance between the competing public and private interests. In particular, the thesis rests on three arguments: the first is the relational-contract nature of dynamic treaty standards, which require the long-term cooperation of the parties. The second is the status of these vague standards as default rules complemented by the provisions of the underlying contracts, which are also relational, and act as gap-fillers. The last, normative argument is that the relationship between these (default) treaty rules and the (gap-filling) contractual provisions should be determined by transaction cost economics, and specifically the goal of economizing on the transaction costs of bounded rationality and opportunism when and interpreting relational treaty standards. La relation entre les traites internationaux d’investissement et les contrats sous-jacents reste un sujet très contentieux dans le domaine du droit international de l’investissement. Cette thèse explore l’interaction entre le contrat et le traité en utilisant la renégociation des contrats règlementaires dans le secteur de l’infrastructure énergétique comme un exemple d’ « expérience naturelle », en se focalisant en particulier sur les litiges arbitraux découlant de la crise économique en Argentine. A cette fin, un cadre analytique original, s’inspirant de l’économie des coûts de transaction et la théorie du contrat relationnel. Le résultat de la combinaison originelle de ces deux cadres analytiques est la construction d’une méthodologie interprétative proposant une approche d’intégration entre les deux instruments – le contrat et le traité – d’une manière apportant plus d’équilibre entre les intérêts publics et privés souvent opposés. La thèse est fondée en particulier sur trois arguments : le premier est la nature des standards dynamiques des traités comme contrats relationnels exigeant la coopération des parties à long terme. Le deuxième est le statut de ces standards vagues comme règles par défaut, complémentés par les provisions des contrats sous-jacents, qui sont aussi relationnels et fonctionnent comme « gap fillers ». Le dernier argument, normatif, est que la relation entre ces règles (par défaut) des traites et les provisions contractuels doit être déterminée par l’économie des coûts de transaction, et en particulier le but d’économiser les coûts de transaction découlant de la rationalité limitée et l’opportunisme durant l’interprétation des standards relationnels des traités.
Keywords: Arbitrage commercial international; Contrats internationaux; Economie des coûts de transaction; Interprétation des traités; Relational contract theory; Théorie du contrat relationnel; Transaction cost economics; Treaty interpretation

The Admissibility of Shareholder Claims: Standing, Causes of Action, and Damages - Bottini, Gabriel (University of Cambridge, 2017)
This thesis addresses risks of multiple recovery, prejudice to legitimate interests of third parties, and inadequate consideration of the applicable law in shareholder claims in investment treaty arbitration. It challenges the application by investment tribunals of two basic premises: i) that shareholders are entitled to claim for damages vis-à-vis measures against the company in which they hold shares and ii) that ‘contract claims’ are to be distinguished from ‘treaty claims’. The central argument is that the failure to recognize substantive overlaps between shareholder treaty claims and contract claims risks more than one recovery, potentially prejudices third parties, and can lead to an incomplete application of the applicable law. The foundations of standing and the cause of action in shareholder treaty claims involve two complementary ideas of independence, i.e., independence of shareholder treaty rights vis-à-vis the local company’s contractual/national law rights and independence of treaty claims vis-à-vis contract claims. However, the substance of shareholder treaty claims, defined as the state measure and particularly the losses involved, is often identical to or at least overlaps considerably with related contract/national law claims. Prevailing ideas on shareholder standing and the cause of action in international investment law have provided useful conceptual tools for jurisdictional determinations. Yet they have not allowed tribunals and the literature to fully consider the implications of shareholder indirect claims. The thesis argues, first, that investment tribunals should acknowledge substantive overlaps between contract and treaty claims. Second, shareholder claims may be inadmissible when such overlap exists and there is a risk of double recovery or prejudice to third parties. Third, the substantive coincidence of treaty and contract claims calls for an integrated approach to the applicable law, where proper weight is given not only to IIA provisions but also to general international law and the national law governing the investment.
Keywords: Admissibility; Admissibility and jurisdiction; Applicable law; Arbitrage; Arbitragem; Arbitration; Contract claims; Contract-treaty distinction; Double recovery; Investment arbitration; Investment claims; Investments; Mixed claims commissions; Prejudice to third parties; Shareholder claims; Shareholder standing; Treaty claims

Conflict of treaty-norms in investment arbitration - Atanasova, Dafina (Université de Genève, 2017)
The study analyses the process through which investment arbitral tribunals identify and resolve conflicts between investment standards of protection and norms from other international regimes relevant for the merits of the dispute. It questions the validity behind the current approach that tribunals adopt, under which arguments based on extraneous norms are overwhelmingly unsuccessful and proposes its' transformation in three respects. First, rather than being a mere means of interpretation, as in current practice, a broader pool of international norms must be applied to the substance of investment disputes. Second, the concept of normative conflict must be broadened if one is to address the actual challenges that inter-regime conflicts pose for international law. Third, fleshing out the modalities under which one could use private international law as a source of inspiration in public international law context, the study offers best practices for approaching the types of conflict commonly found in investment disputes.
Keywords: Arbitrage; Arbitrage d'investissements; Arbitragem; Arbitration; Diversification; Droit international; Droit international privé; Fragmentation; International courts and tribunals; International law; Investissements; Investment arbitration; Investments; Private international law

Dispute resolution in the oil and gas industry: an appraisal of mediation and litigation procedures. - Mohammed, Jamilu Ibn (Journal of private and business law, 2017)
The Oil and Gas Industry Resolution originally recognised negotiation and concede to the alternative dispute resolution rather, their litigation. The paper analysed appraised the different alternative dispute resolution, formulae including mediation the doctrinal method of research which analyses all legal in others as applied. All methods relating to the dispute resolution were analysed from the library and it has formed that mediation which involves the process of resolution dispute weather the involvement of litigating is prefer for being use costly and time consuming. Litigation been so expensive and time wasting is not recommence for oil and Gas Industry.
Keywords: Dispute Resolution; Gas; Industry; Litigation; MARD; Mediación; Mediation; Mediação; Médiation; Oil

Dissenting Opinions in International Commercial Arbitrations - Mohanty, Gautam (Central European University, 2017)
A dissenting opinion with reference to International Commercial Arbitrations elementarily denotes the expression of disagreement by an Arbitrator in relation to both the reasoning and the result of the award granted by the majority of the Tribunal. Though still at a nascent stage, the practice of delivering dissenting opinions is one which needs to be duly noted and taken into due consideration because of the incidental and collateral questions that it nurtures. Fundamentally, a dissenting opinion raises concerns related to the effect, the nature and the rectitude of such opinions. One such collateral question is the enforceability of such dissenting opinions and the repercussions that follow in the context of an arbitral award delivered by the majority. In addition to the above raised question, through this thesis the author will also address other questions such as whether the act of delivering a dissenting opinion is an indicator of the increased sense of maturity of arbitrators in international commercial arbitration? Whether the dissenting opinion possesses any precedential value to the arbitration cases arriving prospectively? and How do such opinions contribute to the development of arbitration jurisprudence. Moreover, through this thesis the author will also attempt from a comparative perspective to examine and make an incisive analysis of the governing rules of arbitration across various arbitration regimes such as ICSID, LCIA which already have a wellestablished arbitration jurisprudence.

Alternative Dispute Resolution (ADR) and access to justice: An introduction - Betancourt, J. (Arbitration, 2017)
Text of a talk given by the author at the University of West London on 8 March 2016 on the topic of Alternative Dispute Resolution, its relation to the concept of access to justice and the idea of practising law in the interest of justice.

The Application of CISG in International Arbitration - Cisár, Ivan (FIRST BRNO ARBITRATION CONFERENCE 2017, 2017)
International arbitration allows great flexibility of the parties to structure their whole relationship. One of the key factors is the choice of the law applicable to the substance of the relationship. CISG is intended for the regulation of such relations between international businessmen. This paper builds on the empirical evidence of the International Arbitration Surveys conducted among various groups of practitioners on their reasoning con cerning choice of law applicable to the substance of the relationship and argues that although CISG is not chosen by them frequently (or arguably not chosen at all), this “omission” is not warranted.
Keywords: CHOICE OF APPLICABLE LAW; CISG; INTERNATIONAL ARBITRATION

Disqualification Decisions under the ICSID Convention and Arbitration Rules - Cleis, Maria Nicole (The Independence and Impartiality of ICSID Arbitrators, 2017)
This Chapter aims to distill a consistent approach to arbitrators’ independence and impartiality from past decisions on disqualification requests. In a first part, the interpretation of the manifest lack requirement provided for in Article 57 icsid Convention is scrutinized. The definition of this threshold (i.e. the burden of proof imposed on the challenging party) is crucial, because it determines the effectiveness of the right to an independent and impartial decision-maker. The second part of the Chapter inquires how specific categories of alleged conflict are dealt with. It seeks to derive consistency and predictability from the outcome or reasoning of disqualification

The Independence and Impartiality of ICSID Arbitrators: Current Case Law, Alternative Approaches, and Improvement Suggestions - Cleis, Maria Nicole (Nijhoff International Investment Law Series, 2017)
In The Independence and Impartiality of ICSID Arbitrators, Maria Nicole Cleis examines the standard of independence required under the ICSID Convention, as evidenced in existing disqualification decisions, and makes novel suggestions for reforms to ensure unbiased decision-making. Readership: All interested in International Investment Law and investor-State arbitration in particular. Readership includes academics, lawyers and arbitrators involved in investment-related disputes (including in-house counsel), treaty negotiators and NGOs.
Keywords: Arbitrage; Arbitragem; Arbitration; Civil procedure; International Arbitration; International disputes; International law

First Brno Arbitration Conference 2017: Current Issues of International Commercial Arbitration (Publications of the Masaryk University, theoretical series, editions Scientia, 2017)
Content research papers : - The Application of CISG in International Arbitration; - CISG and Arbitration in the Hungarian Legal Practice; - Time Limits in Arbitration Agreements : What Can We Expect, if We Fail to Meet Them? - Interpretation Hardships Regarding the CISG, in Particular Article 7; - Awarding Punitive Damages in Czech Arbitration Proceedings; - Award of Legal Costs in Arbitration with Focus on Regulation in the Slovak Republic; - Advantage or a Disadvantage? The Costs of Arbitration Court Proceedings in Hungary.

Alternative Dispute Resolution in Oil and Gas Contracts Law: An Analysis - Kareem, Kareem Kawa (Near East University, 2017)
The industry of oil and gas is not peculiar to question anymore, inferable from the global condition as well as its various dimensions. While trying to complete an agreement procedure, it would barely be clear to expect the thing that could happen in the emergence of a debate. Hazard moving and fragmented contracting lie at the heart of the organization relationship innate in the obtainment and financing of extensive scale undertakings, such as power plants, oil and gas pipelines, and condensed natural gas facilities. An examination of gas bonds gives exact proof of the hazard moving results of legally binding inadequacy. This thesis is a basic examination of the discipline we call the law of oil and gas. A number of the imperfections connected with this "specific" status. Jurisprudential with its "uncommon" status. Jurisprudential imperfections have created as courts leave from essential contract, property, or tort law in quest for natural resources ideas. The marvel isn’t restricted to natural resources law but instead can occur in any "law of" setting. This article delineates the issues connected with oil and gas law by dissecting legal ways to deal with perceiving and applying "inferred agreements" under the oil and gas rent. By contrasting the experience and results under the oil and gas lead to the result under an agreement law investigation, it is conceivable to assess whether a specific "oil and gas" govern is vital or prudent. In the past quarter-century, huge changes have happened in the ways legal advisors approach strife. There have been uncommon endeavors to create systems went for more proficient, not so much expensive, but rather more fulfilling determination of contention, including more broad and suitable utilization of intercession and other " alternative dispute resolution " (ADR) approaches. This review analyzes what is known and not considered about the development and effect of ADR in government and state courts, in the business division, and in work and shopper settings. The investigation inspects the relationship amongst ADR and court trial, additionally underlines the more extensive employments of and method of reasoning for intercession and different process decisions. This study concentrates on the oil and gas contract with question by ADR.

International Arbitration - Liatowitsch, Manuel; Rosenthal, Jeffrey; Forneret, Martine; Scherker, Emily; Ashford, Peter; Janzik, Sabrina; Weldon, Matthew; Houston, Robert; Boog, Christopher; Gottlieb, Benjamin; Meijer, Gerard; Verberne, Valerie; et al. (The Year in Review, 2017)
Keywords: Arbitration; Dispute resolution; International Law

The notion of award in international commercial arbitration-lessons from French and English law - Marchisio, Giacomo (McGill University, 2017)
For the past twenty years, international commercial arbitration scholarship has mainly focusedon the private dimension of international arbitration. Part of a greater movement toward the privatization of justice and law, this understanding of the discipline has obscured arbitrators'adjudicative role. By reflecting on different adjudicative models and by analyzing the form andcontent of arbitral decisions, new light can be shed on our understanding of international commercial arbitration.
Keywords: Arbitrage; Arbitragem; Arbitration; Award; Commercial Arbitration; English law; French law; International Arbitration; International commercial arbitration

Document Production and Disclosure in Investor-State Arbitration - Oepangat, Dioputra Ilham; Janet, Janet (Juris Gentium Law Review, 2017)
It is not uncommon for states to engage in arbitration proceedings with their investors (“Investor-State Arbitration” or “International Investment Arbitration”) administered under the International Centre for the Settlement of Investment Disputes. When these parties engage in document production during evidentiary proceedings, there arises an issue with regards to documents requested by the investor, which is considered as a “state secret” by the state. Based on the IBA Rules on the Taking of Evidence in International Arbitration (“IBA Rules”), states may have particular interest to refuse the production of a document. This is based on the argument that a document may be exempted from production if the document qualifies as a state secret by virtue of Article 9 of the IBA Rules. This paper will discuss appropriate measures to be taken by tribunals in order to allow for material and relevant evidence to be produced during proceedings, which may be crucial in being able to prove the case of the investor in the case of a conflict pertaining to the production of documents containing state secrets.
Keywords: Arbitrage; Arbitragem; Arbitration; Disclose; Document; IBA; ICSID; International; Investments; Prove; Secrets; Sensitive

Can third party funding deliver justice in international commercial arbitration? - Yu, Hong-Lin (International Arbitration Law Review, 2017)
Third party funding arrives at international commercial arbitration without clear guidelines. The recognition and acceptance of its legality is hampered by the omissions of all stakeholders' rights involved in international commercial arbitration. In balancing the funder’s contractual rights to gather information under the third party funding agreement and stakeholders' rights to know, the current research examined how non-disclosure of the third party funding agreement would prevent the arbitrators from fulfilling procedural justice required for the integrity of arbitration on their part and impede the opposing party’s right to know during the proceedings. The research highlights the issues from the delivery of procedural and substantive justice as well as suggesting legal and jurisprudential grounds in third party funding governance. It also points out that all issues examined will ultimately contribute to the failure in delivering justice in international commercial arbitration if third party funding is left to self-governance.
Keywords: Arbitration; International commercial arbitration; Third Party Funding